PENGARUH GAYA KEPEMIMPINAN FEMININ, MOTIVASI KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN PT LEO AGUNG RAYA, SEMARANG - Aprilia Anggraeni, Dena; Rahardja, Edy (Faculty of Economics and Business Diponegoro University, 2018)
Feminism leadership style in a female leader can affect on employee performance. Motivation and commitment of employee can directly affect of high low employees’ performance. The aim of this research is exmine and analysis of existence feminism leadership style on employees’ performance, the influence job motivation on employees’ performance and the influence organizational commitment on employee performance.The research population was the employee of PT Leo Agung Raya thet number 194 employee, then 66 employee were chosen as the sample of the research by using Simple Random Sampling methode. The methode of data analysis used was multiple linear regression analysis. The data testing technique used was test validity, reliability, classical assumption test, T test, F test and coefficient determination testBased on the result of this research, the researcher concludes that the feminism leadership style positively and significantly affect the employees’ performance. The job motivation positively and significantly affect the employees’ performance and the the organizational commitment positevly and significantly affect the employees’ performance